A STYLISTIC ANALYSIS OF FIGURATIVE LANGUAGE IN ARIANA GRANDE’S SONG LYRICS - Nur Fadilla, Devi Ayu Novia; Ariani, Setya; Dewi Max, Jonathan Irene Sartika (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
Figurative language is a language where the conveying of implied meaning is more effective than literal meaning because figurative language provides several effects that help readers to understand the meaning easily. This study aims to analyze the figurative language of Ariana Grande's selected songs in the album Position. To get more immense understanding on how the lyrics are analyzed, Perrine’s theory of figurative language was used. This research used descriptive qualitative research and a stylistic approach. The results showed that nine of twelve types were found such as metaphors, similes, personifications, apostrophes, metonymy, symbols, allegory, paradox and hyperbole. The most frequently type used in the selected song is metaphor. Through the findings mention above, the researcher can conclude that patterns in the selected songs that she always compares herself to luxury objects. This means that the pattern she wants to show in Position album to her listeners is that she tries to love and appreciate herself by comparing herself to luxurious objects such as diamond, Givency, and gold.